2021
DOI: 10.1002/ijop.12801
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy beliefs in Britain and North Macedonia: A comparative study

Abstract: T he psychological research on conspiracy beliefs to date has focused predominantly on conspiracy beliefs in Western democracies. The current study sought to fill this gap by examining beliefs in conspiracy theories in a democratic society and a society in transition. British (N = 298) and Macedonian (N = 312) participants completed an online questionnaire measuring conspiracy beliefs, trust in media and institutions and support for democratic principles. Macedonian participants endorsed conspiracy theories mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…This is to be expected given the nature of conspiracy beliefs, which are often based on distrust in the actions of the government, scientists, and other authorities. It should be mentioned that trust in media and institutions are considered sometimes as antecedents (e.g., Stojanov & Douglas, 2022) and sometimes as consequences of conspiracy beliefs, as is the case in our model. Further longitudinal studies are needed to clarify the direction of this relationship.…”
Section: Discussionmentioning
confidence: 89%
“…This is to be expected given the nature of conspiracy beliefs, which are often based on distrust in the actions of the government, scientists, and other authorities. It should be mentioned that trust in media and institutions are considered sometimes as antecedents (e.g., Stojanov & Douglas, 2022) and sometimes as consequences of conspiracy beliefs, as is the case in our model. Further longitudinal studies are needed to clarify the direction of this relationship.…”
Section: Discussionmentioning
confidence: 89%
“…They comprise both political attitudes (e.g., populism) and the factors shaping them (e.g., political powerlessness), as well as mechanisms of political functioning of individuals (e.g., political ideology). The largest amount of space in this area was dedicated to ideological orientation ( Federico et al, 2018 ; Golec de Zavala and Federico, 2018 ; Hart and Graether, 2018 ; Hollander, 2018 ; Vitriol and Marsh, 2018 ; Enders and Smallpage, 2019b ; Featherstone et al, 2019 ; Calvillo et al, 2020 ; Agley and Xiao, 2021 ; Enders and Uscinski, 2021a ; Furnham, 2021 ; Min, 2021 ; Nera et al, 2021 ; Stecula and Pickup, 2021 ; Stoica and Umbres̨, 2021 ; Tonković et al, 2021 ; Stojanov and Douglas, 2022 ), with extremist ideology distinguished in some studies ( Federico et al, 2018 ; Golec de Zavala and Federico, 2018 ; Baier and Manzoni, 2020 ; Enders and Uscinski, 2021a ; van der Linden et al, 2021 ; Walter and Drochon, 2022 ). Party identification was included in several studies ( Hollander, 2018 ; Vitriol and Marsh, 2018 ; Enders and Smallpage, 2019a , b ; Enders and Uscinski, 2021a ; Stecula and Pickup, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the more commonly used constructs was institutional trust. It was measured most often by the general trust in institutions ( Jasinskaja-Lahti and Jetten, 2019 ; Baier and Manzoni, 2020 ; Eberl et al, 2021 ; Milošević Đorđević et al, 2021a ; Šrol et al, 2021 ; Stojanov and Douglas, 2022 ), but in some studies the institutions were specifically identified, e.g., the parliament ( Vezzoni et al, 2022 ), the World Health Organization ( Freeman et al, 2022 ), the United Nations, the European Union ( Freeman et al, 2022 ), the government ( Freeman et al, 2022 ; Kim and Kim, 2021 ), heath institutions ( Bruder and Kunert, 2022 ), public officials ( Walter and Drochon, 2022 ), or media ( Stojanov and Douglas, 2022 ). In the pandemic situation, the scientific community undertook immediate research ensuring smooth access to medical and social studies on a huge scale.…”
Section: Resultsmentioning
confidence: 99%
“…Even less is known about potential contextual or country‐level predictors of conspiracy theorizing. Conspiracy theorizing has typically been examined in smaller‐scale studies conducted in one country (and typically in WEIRD samples) or has compared conspiracy theorizing across a limited number of countries (e.g., Adam‐Troian et al., 2021; Stojanov & Douglas, 2022). Studies have yet to examine how conspiracy theorizing may vary from place to place according to country‐level differences.…”
Section: Introductionmentioning
confidence: 99%